Complete Chloroplast Genome of Salvia multicaulis Vahl. (Lamiaceae) - Muhammed , Jotyar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate the complete chloroplast (plastome) genome of Salvia multicaulis for the first time in Iraq and surrounding countries. In this study, the complete chloroplast genome was sequenced, assembled, and annotated. Then, phylogenetic analysis was performed. Accordingly, the closely related species were aligned and compared. The circular quadripartite plastome length was 151,373 base pair (bp) includes Large Single-Copy (LSC) region with 82682 bp, and Small Single-Copy (SSC) region with 17,682 bp, and two inverted repeat (IR) regions of 25,592 bp. The complete GC content of the plastome was 38 %. The phylogenetic tree analysis shows that there were two distinct clades. The first clade comprises of the taxa from center-west Asia/ mediterranean region. The second clade includes the East Asia taxa. The S. multicaulis was located on the first clade as a sister group to S. officinalis and S. yangii. Consequently, the analysis of the five clustered species demonstrated that the intergeneric spacers regions were highly variable compared to the coding region.